2019
DOI: 10.1002/biot.201900062
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Energy Storage Devices with Biomacromolecules in Hybrid Electrodes

Abstract: The development of energy storage devices with higher energy and power outputs, and long cycling stability is urgently required in the pursuit of the expanding challenges of electrical energy storage. The utilization of biologically renewable redox compounds holds a great potential in designing sustainable energy storage systems and contributes in reducing the dependence on fossil fuels for energy materials. Quinones are the principal redox centers in natural organic materials and play a key role as charge sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 108 publications
0
13
0
Order By: Relevance
“…The brown–black pigment known as eumelanin plays an important, but uncertain role in melanoma 1 , 2 , whereas the chemically similar neuromelanin is present at greatly reduced levels in the brains of patients with Parkinson’s disease 3 . Very recently, eumelanin-based materials have attracted widespread interest for solar energy conversion, electrochemical energy storage, and biomedical applications 4 6 . Because it absorbs broadly from the UV to near-infrared spectrum and because of its ability to conduct 7 , 8 and store charge, eumelanin is receiving considerable attention for applications including photocatalysis, battery electrodes, and supercapacitors 5 .…”
Section: Introductionmentioning
confidence: 99%
“…The brown–black pigment known as eumelanin plays an important, but uncertain role in melanoma 1 , 2 , whereas the chemically similar neuromelanin is present at greatly reduced levels in the brains of patients with Parkinson’s disease 3 . Very recently, eumelanin-based materials have attracted widespread interest for solar energy conversion, electrochemical energy storage, and biomedical applications 4 6 . Because it absorbs broadly from the UV to near-infrared spectrum and because of its ability to conduct 7 , 8 and store charge, eumelanin is receiving considerable attention for applications including photocatalysis, battery electrodes, and supercapacitors 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Azeredo et al [3] reviewed how biopolymer particles can be utilized as carrier systems for antimicrobials in food packaging. Further reviews by Santos et al [4] and Ajjan et al [5] discuss the design of biopolymer-based materials as bioabsorbent for the cleanup of polluted water or for the development of renewable biohybrid electrodes to combat energy storage challenges, respectively. Extraction and processing of biopolymer are important for cost-effective manufacturing and applications, respectively.…”
Section: Doi: 101002/biot201900500mentioning
confidence: 99%
“…Further reviews by Santos et al . and Ajjan et al . discuss the design of biopolymer‐based materials as bioabsorbent for the clean‐up of polluted water or for the development of renewable biohybrid electrodes to combat energy storage challenges, respectively.…”
mentioning
confidence: 99%
“…[10,12] Many studies in the literature have reported on the use of organic redox materials, to enhance the supercapacitive performance beyond that provided by EDLs. [13,14] Organic materials with redox active groups, such as phenol, carbonyl, quinones, carboxy, or amines [5] are becoming promising candidates for next-generation sustainable energy Organic electrode materials operating in aqueous electrolytes offer the opportunity to avoid toxic, critical, and expensive materials for electrochemical energy storage. When deposited on carbon current collectors, redox active organic materials add faradaic to electrostatic capacitance contribution to the electrodes.…”
mentioning
confidence: 99%
“…storage devices. [14,15] Further, they can be used in environmentally friendly, inexpensive and non-corrosive neutral aqueous electrolytes. [16] Quinones are a class of organic molecules ubiquitous in nature.…”
mentioning
confidence: 99%